Lycomimodes, a new generic replacement name for preoccupied Lycomimus Lawrence and Slipinski, 2013 (Insecta: Coleoptera: Ptilodactylidae) non Melzer, 1931 (Insecta: Coleoptera: Cerambycidae) - Lawrence, John F.; Slipinski, Adam (Zootaxa, 2013)
The generic name Lycomimus (L. bejsaki Lawrence and Slipinski 2013, by original designation) was proposed by Lawrence and Slipinski (2013, p. 71) for a new coleopteran genus from northern New South Wales and southern Queensland, Australia. However, this name is already preoccupied by Lycomimus Melzer (1931, p. 11). To resolve homonomy, in accordance with the International Code of Zoological Nomenclature, Lycomimodes nom. nov. (type species Lycomimus bejsaki Lawrence and Slipinski, 2013) is here proposed as a replacement name for Lycomimus Lawrence and Slipinski 2013, non Melzer. The name is derived from the beetle family Lycidae, the Greek mimos, actor and the Greek suffix odes denoting likeness; the gender is masculine.